2002
DOI: 10.1248/bpb.25.1315
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nitric Oxide to Potassium Bromate-Induced Elevation of Methaemoglobin Concentration in Mouse Blood.

Abstract: Bromate is frequently detected in tap water and bottled water, since it is an inorganic oxyhalide disinfection by-product, which is formed when drinking water supplies undergo ozonation, an advanced wastewater treatment technique. 1,2) Potassium bromate (KBrO 3 ) is a renal carcinogen and is classified as a group 2B (possibly carcinogenic to humans) by the International Agency for Research on Cancer, 3,4) as are bleomycin and carbon tetrachloride, etc. However, KBrO 3 is generally used as an oxidizing agent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In the present study, KBrO3 at concentrations <250 µM induced cardiac hypertrophy without apoptosis in a cultured cell line. Additionally, it was demonstrated that free radicals and/or oxidative stress were mediated by the effect of KBrO3, which is fully consistent with previous reports that KBrO3 induces damage via oxidative stress (10)(11)(12). Cardiac injury induced by KBrO3 has also been observed in rats (15,16), and histological evidence demonstrates that KBrO3 induces cardiac apoptosis and/or necrosis in rodents (33).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, KBrO3 at concentrations <250 µM induced cardiac hypertrophy without apoptosis in a cultured cell line. Additionally, it was demonstrated that free radicals and/or oxidative stress were mediated by the effect of KBrO3, which is fully consistent with previous reports that KBrO3 induces damage via oxidative stress (10)(11)(12). Cardiac injury induced by KBrO3 has also been observed in rats (15,16), and histological evidence demonstrates that KBrO3 induces cardiac apoptosis and/or necrosis in rodents (33).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, KBrO3 induced cardiac hypertrophy in H9c2 cells. ROS produced by KBrO3 are proposed as the primary mediators in tissue damage (11,16). Thus, the changes in ROS and superoxide levels were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KBrO 3 caused a dramatic increase in MetHb formation at all concentrations used. Watanabe et al () have also reported increased MetHb levels in the plasma of mice that were orally administered bromate. Significantly, we have found that the activity of MetHb reductase, enzyme involved in the conversion of MetHb back to Hb, was increased showing that elevated levels of MetHb are not due to inhibition of this enzyme.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, certain antioxidant substances, e.g., ebselen 11 or melatonin, 12 have already been shown to protect against oxidative damage, caused by KBrO 3 . Melatonin (N-acetyl-5-methoxytryptamine)-the pineal hormone-is an effective antioxidant and free radical scavenger.…”
mentioning
confidence: 99%